The Utilization of Fermented Vegetable Waste on Dry Matter and Organic Matter Digestibility on Local Sheep Feed - P H I Meliala; Hasnudi Hasnudi; S Umar; N Ginting; A Hakim Daulay (Jurnal Peternakan Integratif, 2017)
Abstract. The study objective was to analyze the value of dry matter and organic matter of fermented vegetable waste on local sheep feed. Research conducted at the Laboratory of Animal Biology and the Laboratory of Nutrition and Feed Science, Animal Science Study Program, Faculty of Agriculture, University of Sumatera Utara, in June - September 2016. The research used local sheep with the average of body weight 13,4 ± 1,2 kg. The design experimental used completely randomized design (CRD) with 5 treatments and 4 replications. The treatment were ratio grass with fermented vegetable waste, composed of P0 (100 : 0), P1 (75 : 25), P2 (50 : 50), P3 (25 : 75) and P4 (0 : 100). Variable were measured i.e consumption of dry matter and organic matter and digestibility of dry matter and organic matter.Results of analysis of variance showed that the utilisation of fermented vegetable waste had highly significantly different effect (P<0,01) on dry matter and organic matter digestibility. Increasing utilization fermented vegetable waste increase dry matter and organic matter digestibility on local sheep feed. The conclusion of this study is the use of fermented vegetable waste can increase the digestibility of dry matter and organic matter on local sheep. Keywords: Waste Vegetable, Fermentation, Digestibility, Local Sheep